2017
DOI: 10.2147/ijgm.s137469
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of sputum smear-positive but culture-negative results among newly diagnosed pulmonary tuberculosis patients in Tanzania

Abstract: Diagnosis of pulmonary tuberculosis (TB) in technology-limited countries is widely achieved by smear microscopy, which has limited sensitivity and specificity. The frequency and clinical implication of smear-positive but culture-negative among presumptive TB patients remains unclear. A cross-sectional substudy was conducted which aimed to identify the proportion of nontuberculous mycobacteria (NTM) infections among 94 “smear-positive culture-negative” patients diagnosed between January 2013 and June 2016 in se… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
15
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 19 publications
(18 citation statements)
references
References 26 publications
0
15
0
Order By: Relevance
“…Effective TB control interventions require early identification of TB infected persons and tailored therapies. As a result of limited performance of smear microscopy [ 1 , 2 ] and a slow generation time of mycobacteria on culture media [ 3 ], the WHO endorsed the use of GeneXpert MTB/RIF for rapid detection of TB and rifampicin resistance [ 4 ]. As rapid diagnostic tools become available, the main challenge remains on how responsive the health system is to ensure effective linkage of diagnosed patients to requisite healthcare.…”
Section: Introductionmentioning
confidence: 99%
“…Effective TB control interventions require early identification of TB infected persons and tailored therapies. As a result of limited performance of smear microscopy [ 1 , 2 ] and a slow generation time of mycobacteria on culture media [ 3 ], the WHO endorsed the use of GeneXpert MTB/RIF for rapid detection of TB and rifampicin resistance [ 4 ]. As rapid diagnostic tools become available, the main challenge remains on how responsive the health system is to ensure effective linkage of diagnosed patients to requisite healthcare.…”
Section: Introductionmentioning
confidence: 99%
“…It is best to inform the microbiologist about the suspicion so that appropriate tests are carried out. Another important feature in NTM infections that helps in early diagnosis is a positive smear for acid-fast bacilli and negative GeneXpert [ 75 , 76 , 77 , 78 , 79 , 80 ]. The incidence of these infections is sizeable.…”
Section: Discussionmentioning
confidence: 99%
“…This can be attributed to the use of suboptimal diagnostic tests, particularly in developing countries like Tanzania. The detection of acid-fast bacilli by smear examination of NTM can result in the misdiagnosis of TB cases (Hoza et al, 2016a,b;Mfinanga et al, 2014;Kilale et al, 2016;Mnyambwa et al, 2017a), which normally do not respond to anti-TB drugs, thereby leading to classification as MDR-TB (Lu et al, 2016;Shahraki et al, 2015). Most of the MAC members are naturally resistant to anti-TB drugs (Shahraki et al, 2015;Mpagama et al, 2013), which leads to the unnecessary administration of toxic second-line anti-TB treatments, thereby increasing the risk of the evolution of drug resistance.…”
Section: Discussionmentioning
confidence: 99%
“…The authors also revealed that members of M. yongonense Type I genotype harbour a unique DNA mismatch repair gene MutS4 family, that potentially serves as a putative driving force for the suggested HGT between the M. parascrofulaceum and M. yongonense Type I genomes through homologous recombination events (Kim et al, 2017). The occurrence of NTM in Tanzania has been reported frequently (Hoza et al, 2016a,b;Mfinanga et al, 2014;Kilale et al, 2016;Mnyambwa et al, 2017a), but characterization of the isolates has relied on suboptimal typing methods that have potentially hindered accurate species identification.…”
Section: Introductionmentioning
confidence: 99%